PENGARUH PENAMBAHAN PROBIOTIK Lactobacillus sp. PADA PAKAN PELET TERHADAP PERTUMBUHAN IKAN KERAPU CANTANG (Epinephelus fuscoguttatus >< Epinephelus lanceolatus) - Yani, Kadek Linda; Marantika, Alexander Korinus; Maharani, Made Dwipa Kusuma (Program Studi Akuakultur, Universitas Bangka Belitung, 2025)
The demand for Cantrang hybrid grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) continues to increase, prompting various efforts to improve its productivity. One of the main challenges in hybrid grouper aquaculture is the provision of high-quality feed, which is a crucial factor for the success of cultivation activities. This study aimed to evaluate the effect of adding Lactobacillus sp. probiotics to pellet feed on the growth performance of hybrid grouper. The research was conducted at the Center for Marine Aquaculture Research and Fisheries Extension (BBRBLPP) in Gondol, Bali. A completely randomized design (CRD) was used with four treatments and three replications: Treatment K (pellets without probiotics), Treatment A (5 g/kg probiotics), Treatment B (10 g/kg probiotics), and Treatment C (15 g/kg probiotics). Data were analyzed using one-way ANOVA followed by Tukey’s post-hoc test. The results showed that Treatment B (10 g/kg probiotics) yielded the best outcomes, with an average length increase of 2.08 cm, weight gain of 2.6 g, feed conversion ratio (FCR) of 0.9, and 100 % survival rate. Based on these findings, it is recommended to use Lactobacillus sp. probiotics at a dose of 10 g/kg feed to improve growth, reduce feed conversion ratio, and enhance fish survival.